PENGEMBANGAN KURIKULUM PAI BERBASIS KOMPETENSI UNTUK PENINGKATAN KARAKTER PESERTA DIDIK - Jaslainy; Nani Hayda Fitri; Rosniati Hakim; Ahmad Lahmi (STKIP Subang, 2026)
This study aims to describe and analyze the development of a competency-based Islamic Education (PAI) curriculum as an effort to enhance students’ character. The urgency of this research is based on the increasingly complex moral and social challenges faced by the younger generation, indicating that Islamic Education learning should not only focus on mastery of subject matter but also on the formation of attitudes and behaviors. This study employs a qualitative approach using a library research method and descriptive analysis of the concept of competency-based curriculum and its implementation in Islamic Education learning. The findings reveal that a competency-based PAI curriculum emphasizes the integration of spiritual attitudes, social attitudes, knowledge, and skills. The strengthening of students’ character is carried out through the integration of religious values, honesty, discipline, responsibility, and tolerance into learning objectives, learning materials, active learning strategies, and authentic assessment systems. Therefore, the development of a competency-based PAI curriculum plays a strategic role in shaping students who possess strong character, noble morals, and the ability to internalize and practice Islamic values in their daily lives.